A comparison of the capacities of VR and 360-degree video for coordinating memory in the experience of cultural heritage - Cai, Shengdan; Ch'ng, Eugene; Li, Yue (2018)
Virtual Reality (VR), a medium which can create alternate or representations of reality, could potentially be used for triggering memory recollections by connecting users with their past. Comparing to commonly-used media within museum such as photos and videos, VR is distinct because of its ability to move beyond the confines of time and space, by enabling users to be immersed in the reconstructed context and allowing them to take charge of the environment by interacting with objects, navigating the environment, and evolving the narratives. In this paper, we compared audience experiences of cultural heritage (CH) between 360-degree video recordings and Virtual Environments to investigate the capacity of these two types of media for coordinating the audience’s memory of the past. The findings will help guide the future design and evaluation of VR as a medium for communicating CH.